An interlaboratory comparison of dosimetry for a multi-institutional radiobiological research project: Observations, problems, solutions and lessons learned. (1st February 2016) - Seed, Thomas M.; Xiao, Shiyun; Manley, Nancy; Nikolich-Zugich, Janko; Pugh, Jason; Van den Brink, Marcel; Hirabayashi, Yoko; Yasutomo, Koji; Iwama, Atsushi; Koyasu, Shigeo; Shterev, Ivo; Sempowski, Gregory; et al.
Abstract: Purpose : An interlaboratory comparison of radiation dosimetry was conducted to determine the accuracy of doses being used experimentally for animal exposures within a large multi-institutional research project. The background and approach to this effort are described and discussed in terms of basic findings, problems and solutions. Methods : Dosimetry tests were carried out utilizing optically stimulated luminescence (OSL) dosimeters embedded midline into mouse carcasses and thermal luminescence dosimeters (TLD) embedded midline into acrylic phantoms. Results : The effort demonstrated that the majority (4/7) of the laboratories was able to deliver sufficiently accurate exposures having maximum dosing errors of ≤5%. Comparable rates of 'dosimetric compliance' were noted between OSL- and TLD-based tests. Data analysis showed a highly linear relationship between 'measured' and 'target' doses, with errors falling largely between 0 and 20%. Outliers were most notable for OSL-based tests, while multiple tests by 'non-compliant' laboratories using orthovoltage X-rays contributed heavily to the wide variation in dosing errors. Conclusions : For the dosimetrically non-compliant laboratories, the relatively high rates of dosing errors were problematic, potentially compromising the quality of ongoing radiobiological research. This dosimetry effort proved to be instructive in establishing rigorous reviews of basic dosimetry protocols ensuring that dosing errors were minimized.